The Socialization Process in Reading Clubs During the Pandemic Period - Oliveira, Beatriz Lima (2024)
It addresses reading and socialization through reading groups, seeking to understand how reading and book clubs work. Its main objective is to analyze the socialization process in these groups developed in the period between 2020 and 2022, emphasizing how the interaction takes place and how the reading experiences helped to overcome the pain caused by the pandemic. Its specific objectives are: to reflect on the development of reading practices; and analyze how reading experiences helped overcome the pain caused by the Pandemic. The methodological path was based on an exploratory and descriptive research, with a qualitative approach, questionnaire and content analysis. It is concluded that group reading represented an escape from the atypical reality experienced, with the sharing of experiences and experiences.